Diversity of pollinators in marigold (Tagetes erecta L.) in a core area of Kathmandu Valley, Nepal (Nepal Journal of Environmental Science, 2020)
Insect pollinators provide crucial ecosystem services in the urban environment but are under threat and lack comprehensive study and Pollinators’ interaction to change urban land use. Marigold is an important nectar provider for many insects, plays a major role in ecosystem services, and holds a strong cultural and economic value. Therefore, it is important to learn the diversity of insect pollinators in marigolds in an urban environment and assess the impact of urbanization on pollinators. This study aimed to study pollinator diversity, visit frequency, and shift-wise distribution in the core urban area of Kathmandu valley. A total of 21 species of pollinators were recorded from fourteen families and four orders: Hymenoptera, Diptera, Lepidoptera and Coleoptera. Lepidoptera accounted for the highest diversity index of 1.87 followed by Diptera. Furthermore, the study recorded the highest species diversity and abundance during the daytime compared to the morning and the evening hour. The highest diversity of Diptera and Lepidoptera suggests that the urban area is a suitable foraging area whereas, the absence of wild bees further suggests the urbanization as a threat to the wild bee population and demand urgent policy or action for the conservation of pollinators for the conservation of biodiversity and growth in agricultural production.